2020
DOI: 10.1186/s12941-019-0343-8
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella pneumoniae: an increasing threat to public health

Abstract: Objectives: This review fills the paucity of information on K. pneumoniae as a nosocomial pathogen by providing pooled data on epidemiological risk factors, resistant trends and profiles and resistant and virulent genes of this organism in Asia. Methods:Exhaustive search was conducted using PubMed, Web of Science, and Google scholar for most studies addressing the prevalence, risk factors, drug resistant-mediated genes and/or virulent factors of K. pneumoniae in Asia. Data extracted for meta-analysis were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
254
3
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(275 citation statements)
references
References 53 publications
14
254
3
4
Order By: Relevance
“…Another example of the opportunistic pathogens causing a broad spectrum of diseases and showing increasingly frequent acquisition of resistance to antibiotics is Klebsiella pneumoniae [ 20 ]. Hameed et al [ 90 ] tested chemically synthesized ZnO NPs doped with Nd against K. pneumoniae —the minimal inhibitory concentration was found to be 1000 μg/mL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example of the opportunistic pathogens causing a broad spectrum of diseases and showing increasingly frequent acquisition of resistance to antibiotics is Klebsiella pneumoniae [ 20 ]. Hameed et al [ 90 ] tested chemically synthesized ZnO NPs doped with Nd against K. pneumoniae —the minimal inhibitory concentration was found to be 1000 μg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, antibiotic resistance among pathogenic bacteria is a real problem for humanity [ 17 , 18 , 19 ]. The increasing problem of drug-resistance among many pathogens, e.g., Staphylococcus aureus , Pseudomonas aeruginosa, Klebsiella pneumonia or Escherichia coli, requires the development of novel antiseptics [ 20 , 21 , 22 , 23 ]. One of the prospective alternatives to antibiotics is, as proposed in our study, the post-cultured synthesis of zinc oxide nanocomposites by lactic acid bacteria isolated from whey.…”
Section: Introductionmentioning
confidence: 99%
“…pneumoniae outbreaks. The emergence of K. pneumonia carrying carbapenemases and their worldwide dissemination represent significant public health crisis 26 . As carbapenem resistance bla KPC-2 and bla NDM-1 are the most widely reported among CRKP worldwide, we used genomic and phylogenetic approaches to analyze CRKP isolated from hospital in China and uncover the distribution of these two genes in global genomes from GeneBank of NCBI.…”
Section: K Pneumoniae Is Responsible For Human Infections and Patienmentioning
confidence: 99%
“…[2] A meta-analysis published in 2020 confirmed that the trend in the isolation rate of K. pneumoniae is increasing and there is a rapid global emergence of strains of this organism resistant to almost all antibiotics, including carbapenems. [3] The main resistance mechanism responsible for antibiotic resistance is the production of Klebsiella pneumoniae carbapenemases (KPCs), βlactamases belonging to class A. β-lactamases form an acylenzyme adduct with the antibiotic, which is then easily hydrolyzed by a water molecule; thereby, the drug is made ineffective (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%